Making the Korean nation in the Russian Far East, 1863-1926 - Sablin, Ivan; Kuchinsky, Alexander (Nationalities papers, 2018)
Exploring the history of Koreans in the Russian Far East from the perspective of New Imperial History, the article demonstrates that political activism of Koreans and policies of the Russian (Soviet), Korean, and Japanese governments resulted in consolidation of two visions of their future. The first vision implied unity between the Koreans living in the Russian Far East with those who stayed in Korea, moved to Japan, or emigrated elsewhere and corresponded to the agenda of building a Korean nation. The second vision implied that the bilingual or Russified Koreans aspired to stay in the Russian Far East permanently, ensuring their own livelihood in the new regional frontier. The two currents interlaced in the project of Korean autonomy in a post-imperial state, first the Far Eastern Republic and later the Union of the Soviet Socialist Republics. The project involved inclusion of Koreans into the global spread of revolution through the Communist International and left open the issue of the duration of Korean presence in the Russian Far East. Its ultimate failure in 1926 left the Koreans partly excluded from the Soviet system without the institutional benefits of national autonomy.
Published online: 20 November 2018
Gesehen am 27.05.2019